The Disposal of Impurity in the Priestly Writings of the Bible, with Reference to Similar Phenomena in Hittite and Mesopotamian Cultures - Wright, David Pearson (1984)
Ph.D. diss.; Order No. DA8427133. Cf. DissAbstr 45 (1985) 2972-A.